Influence Of Professional Development Programmes On Basic School Teachers’ Classroom Practices In North-Central Nigeria - Abdul Ganiyu Alabi (Universitas Bengkulu, 2021)
This paper evaluated the influence of PDP on Basic School Teachers’ Classroom Practices in North-Central, Nigeria. The study adopted a descriptive survey design. In selecting samples for this study, 746 basic school teachers were purposively selected from 84 sampled Basic Schools across three sampled states using stratified sampling technique out of the six states and Federal Capital Territory, Abuja. The Questionnaire “Influence of Professional Development Programmes ”(IPDP) with reliability index of 0.74 was used. One - Way Analysis of Variance was used to test the hypothesis at 0.05 level of significance. The findings of the study revealed no significance influence of teachers’ participation in PDPs on psychomotor and affective classroom practices based on experience (F (2,724) = .018, p = 982); and F(2,724) =.628, p = .534) were observed .Consequently, teachers’ participation in PDPs had no significant influence in psychomotor and affective classroom practices based on years of experience. There is need to make the programme more effective in term of organization and implementation as antidotes to the hindrances confronting the PDPs in North-Central, Nigeria.